Developing political capabilities with Community-Based Monitoring for health accountability: The case of the Mahila Swasthya Adhikar Manch. Issue 12 (2nd December 2018) - Balestra, Giulietta Luul; Dasgupta, Jashodhara; Sandhya, Yatirajula Kanaka; Mannell, Jenevieve
ABSTRACT: Community-Based Monitoring (CBM) is a participatory process in which citizens gather evidence on services to hold governments accountable to their commitments. Research on CBM for health in developing countries has mostly measured its impact on service performance. Overall, these studies have produced mixed evidence of CBM's effectiveness. This has led some authors to question the role of civic engagement, especially in communities where expectations from public services and power to demand for change are low. This conclusion, we argue, overlooks the role of the CBM process in fostering both participation and social change. Drawing from qualitative research with the Indian grassroots women's organisation Mahila Swasthya Adhikar Manch, we argue that CBM can foster political capabilities through mediating communities' relationships with the state as well as relationships within communities. The engagement of women and their power to demand for change in the health sector and beyond emerges at the intersection of these two spheres. This suggests that measuring the impact of CBM on health services is not sufficient. Expanding the focus of research on CBM to its process is necessary to fully understand the role of civic engagement and to restore its political relevance.